For and against Abelard : the invective of Bernard of Clairvaux and Berengar of Poitiers - Thomson, R. M.; Thomson, R. M.; Winterbottom, M.; Winterbottom, M. (Boydell Medieval texts., 2020)
The famous letters of Bernard of Clairvaux attacking the philosopher Peter Abelard and a vituperative response to them are presented together for the first time.